Mutation Analysis of L‐Thymidine‐Induced Replication Products Using a Restriction Enzyme–Mediated Assay. Issue 1 (8th December 2020) - Kan, Yuhe; Wu, Li; He, Yujian
Abstract: This article describes experimental and analytical procedures for evaluating the efficiency and fidelity of DNA replication containing mirror‐image thymidine (L ‐T) in E. coli . The procedure involves construction of DNA recombinants containing a restriction enzyme (PstI) recognition site in which the L ‐T lesion is site‐specifically located within the PstI recognition sequence (CTGCAG). The recombinants are transfected into DH5α cells. DNA is extracted, amplified, and cleaved into relatively short fragments using different combinations of restriction enzymes to facilitate electrophoretic analysis. Detailed explanations for the restriction enzyme–mediated assay for detection of mutagenic properties of mirror‐image thymidine at a predetermined site are also presented. Advantages and limitations of the assay are discussed by comparing it to other techniques used for detecting lesion‐induced mutation efficiency, and a troubleshooting guide is provided. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of oligonucleotides containing L ‐T Basic Protocol 2 : Construction of DNA recombinants Basic Protocol 3 : Mutation analysis of L ‐T‐induced replication products using a restriction enzyme–mediated assay